Rompendo o silêncio: acolhimento de denúncias de assédio sexual em uma universidade pública federal brasileira - Oliveira, Lucila Batista (2023)
Sexual harassment is one of the many types of gender violence suffered by women in society, including universities. As a result of gender discrimination and the asymmetry of power relations, sexual harassment in academia must be studied in order to understand it as a phenomenon that needs to be fought, not silenced, so that this environment becomes a less hostile and more inviting place for women who want to study and pursue a career in higher education. However, while machismo and patriarchy cannot be overcome, institutions need to offer mechanisms for reporting sexual harassment to break the cycle of impunity and prevent new victims. In this research, we explore how a Brazilian federal public university administratively handles reports and complaints of sexual harassment against women at the institutional level, based on the reality of a federal public university in the North region of Brazil. Through a case study, the research corpus consisted of document analysis and 24 interviews, which were analyzed using the content analysis technique according to Bardin. As a result, we arrived at the following categories: "Sexual Harassment: Concept and Understanding", "Formal Structure", "Barriers to Reporting" and "Not Everything is a Barrier", which helped us to know how the university is organized to assist victims of sexual harassment and to conclude that, although federal universities have formal structures and legal bases to receive and investigate such complaints, there are still barriers to be overcome so that women, the main victims of sexual harassment, feel safe when denouncing the cases that have occurred in academic institutions. In addition, with the findings of this research, we developed a protocol for receiving complaints of sexual harassment, considering the particularities of Brazilian federal universities, which are not always addressed in documents produced by the Federal Government on the subject.